Motives for Physical Activity among Deaf Students: A Descriptive Analysis - Ekawati, Febriani Fajar; Tri Winarti Rahayu; Budhi Satyawan; Ismaryati; Deddy Whinata Kardiyanto; Bambang Wijanarko (INKLUSI, 2025)
Participation in physical activity offers important health and social benefits for Deaf students, including opportunities for skill development, social interaction, and enhanced self-confidence. However, limited attention has been given to the motivational factors that shape their engagement in physical activity within inclusive education contexts. This study aimed to examine the types of motivation influencing Deaf students’ participation in sports and physical activities. Employing a quantitative descriptive design, the study involved 43 Deaf students aged 12–19 years who completed an adapted version of the Motives and Barriers for Physical Activity and Sport (MBAFD) questionnaire. The findings indicated that intrinsic motivation—particularly enjoyment, learning new movements, and perceived well-being—emerged as the dominant factor driving participation in physical activity. These results underscore the importance of fostering autonomy-supportive and enjoyable physical education environments to promote sustained engagement among Deaf students and inform the development of more inclusive and context-responsive physical education practices. Partisipasi dalam aktivitas fisik memberikan manfaat kesehatan dan sosial yang penting bagi siswa Tuli, termasuk pengembangan keterampilan, peningkatan interaksi sosial, dan penguatan kepercayaan diri. Namun, kajian yang secara khusus menelaah faktor-faktor motivasional yang memengaruhi keterlibatan siswa Tuli dalam aktivitas fisik masih terbatas, khususnya dalam konteks pendidikan inklusif. Penelitian ini bertujuan untuk mengkaji jenis motivasi yang memengaruhi partisipasi siswa Tuli dalam aktivitas olahraga dan aktivitas fisik. Penelitian ini menggunakan desain kuantitatif deskriptif dengan melibatkan 43 siswa Tuli berusia 12–19 tahun yang mengisi kuesioner Motives and Barriers for Physical Activity and Sport (MBAFD) versi adaptasi. Hasil penelitian menunjukkan bahwa motivasi intrinsik, terutama yang berkaitan dengan kesenangan, pembelajaran gerak baru, dan persepsi kesejahteraan, merupakan faktor dominan yang mendorong partisipasi aktivitas fisik. Temuan ini menegaskan pentingnya pengembangan lingkungan pendidikan jasmani yang mendukung otonomi, menyenangkan, dan responsif terhadap kebutuhan siswa Tuli guna mendorong keterlibatan yang berkelanjutan serta memperkuat praktik pendidikan jasmani inklusif.